Developing and deploying climate-resilient maize varieties in the developing world. (October 2018) - Cairns, Jill E; Prasanna, BM
Graphical abstract: Highlights: Climate-resilient maize has the potential to increase yield by 5–25% in Africa. Establishment of a large managed stress screening network facilitated gains in grain yield in stress-prone environments. Timelines for replacing old varieties with improved climate resilient varieties are reducing. Higher genetic gain and faster variety replacement required to increase yield and climate resilience. Abstract : In sub-Saharan Africa (SSA) and Asia maize yields remain variable due to climate shocks. Over the past decade extensive progress has been made on the development and delivery of climate-resilient maize. In 2016 over 70 000 metric tonnes of drought-tolerant maize seed was commercialized in 13 countries in SSA, benefiting an estimated 53 million people. Significant progress is also being made with regard to the development and deployment of elite heat-tolerant maize varieties in South Asia. Increased genetic gain in grain yield under stress-prone environments, coupled with faster replacement of old/obsolete varieties, through intensive engagement with seed companies is essential to protect maize crops grown by smallholders from the changing climates in SSA and Asia.